ИҚТИСОДИЁТНИНГ ГЛОБАЛЛАШУВИ ШАРОИТИДА ТАБИИЙ БОЙЛИКЛАРДАН ФОЙДАЛАНИШДА ЭКОЛОГИК МЕНЕЖМЕНТНИНГ НАЗАРИЙ ВА МЕТОДОЛОГИК АСОСЛАРИ (Scientific journal of the Fergana State University, 2023)
The article discusses the general issues of the formation of environmental management in the conditions of ensuring the stability of the surrounding natural environment. In the course of the presentation of the work, the main elements of environmental management are generalized and structured, its functions are systematized, the factors of its evolutionary development are classified, as well as the role of environmental management in the formation of a platform for sustainable development of the national economy